MANAJEMEN KEPALA SEKOLAH DALAM MENERAPKAN BUDAYA RELIGIUS DI SMA NEGERI 2 SIJUNJUNG - Zulhendri Zulhendri (IAIN Batusangkar, 2018)
This study aims to describe the form of religious culture applied in SMA Negeri 2 Sijunjung and how the principal in implementing religious culture. The type of research used is qualitative descriptive. Informant research as many as 8 people. Data collection tools are researchers as key instruments and supporting instruments are interview guides, observation guides, field notes, and hp. Data collection techniques are participatory observation, in-depth interview and documentation study. Data analysis technique using Spradley (1980) model is doing domain analysis, carrying out taxonomic analysis, doing component analysis and doing theme analysis. Techniques of testing the validity of data using triangulation of data and methods. The results showed that starting planning, organizing, implementing and supervising religious programs such as Zuhr prayers in congregation, zikir and prayer, tadarrus al-qur'an, culture 5S, and infak and gebu program applied in SMA Negeri 2 Sijunjung, head the school always involves all the citizens of the school ranging from teachers, education personnel, school committees, and security guards. It is implemented by the school principal and the whole school community through chanting, habituation, giving advice (motivation), and the commemoration of Islamic day (PHBI). So that these religious activities can run well in SMA Negeri 2 Sijunjung.